2008
DOI: 10.1359/jbmr.080110
|View full text |Cite
|
Sign up to set email alerts
|

Doubly Truncated FosB Isoform (Δ2ΔFosB) Induces Osteosclerosis in Transgenic Mice and Modulates Expression and Phosphorylation of Smads in Osteoblasts Independent of Intrinsic AP-1 Activity

Abstract: ABSTRACT:Introduction: Activator protein (AP)-1 family members play important roles in the development and maintenance of the adult skeleton. Transgenic mice that overexpress the naturally occurring ⌬FosB splice variant of FosB develop severe osteosclerosis. Translation of ⌬fosb mRNA produces both ⌬FosB and a further truncated isoform (⌬2⌬FosB) that lacks known transactivation domains but, like ⌬FosB, induces increased expression of osteoblast marker genes. Materials and Methods:To test ⌬2⌬FosB's ability to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 61 publications
1
39
0
Order By: Relevance
“…We thus conclude that ⌬FosB and/or ⌬2⌬FosB positively regulate cell-matrix adhesion as well as TGF-␤1 signaling, whereas FosB negatively regulates them. Recently, it has been reported that ⌬2⌬FosB and to a lesser extent ⌬FosB modulate the expression and phosphorylation of Smads independent of intrinsic AP-1 activity (Sabatakos et al, 2008), confirming that both ⌬FosB and ⌬2⌬FosB play important roles in the up-regulation of TGF-␤1 signaling, as we observed in the present study.…”
Section: Down-regulation Of Cell-matrix Adhesion and Tgf-␤1supporting
confidence: 92%
See 2 more Smart Citations
“…We thus conclude that ⌬FosB and/or ⌬2⌬FosB positively regulate cell-matrix adhesion as well as TGF-␤1 signaling, whereas FosB negatively regulates them. Recently, it has been reported that ⌬2⌬FosB and to a lesser extent ⌬FosB modulate the expression and phosphorylation of Smads independent of intrinsic AP-1 activity (Sabatakos et al, 2008), confirming that both ⌬FosB and ⌬2⌬FosB play important roles in the up-regulation of TGF-␤1 signaling, as we observed in the present study.…”
Section: Down-regulation Of Cell-matrix Adhesion and Tgf-␤1supporting
confidence: 92%
“…It has been shown that expression of the Tgfb1i1 gene is regulated by RAR as well as by TGF-␤1, both of which can modulate AP-1 function (Liberati et al, 1999;Zhou et al, 1999;Suzukawa and Colburn, 2002;Zhuang et al, 2003), suggesting that expression of Tgfb1i1 is indirectly regulated by FosB or ⌬FosB/⌬2⌬FosB through their interaction with steroid receptors or Smad proteins, as reported recently (Sabatakos et al, 2008). Furthermore, it has been shown that Hic5/ARA55 itself negatively regulates Smad3 signaling (Wang et al, 2005).…”
Section: Down-regulation Of Cell-matrix Adhesion and Tgf-␤1mentioning
confidence: 74%
See 1 more Smart Citation
“…To examine BMP2 responses, cells were maintained in 0.5% fetal bovine serum and treated with 100 ng/ml BMP2 or vehicle 16 h prior to assay. Flag-Ebf1, Smad1, and Smad4 constructs were described previously (22,32). Zfp521 deletion constructs (21) were kind gifts from D. Kamiya and Y. Sasai.…”
Section: Mice Zfp521mentioning
confidence: 99%
“…First we generated mice with a heterozygous germline deletion of Zfp521 (Zfp521 We sought to further investigate the Zfp521-mediated antagonism of Runx2 activity by generating bitransgenic mice in which overexpression of Zfp521 was regulated by the enolase 2 (ENO2) promoter (ENO2-tTA;TetOp-Zfp521 mice, hereafter referred to as Zfp521 Tg mice). We successfully used this bitransgenic system in earlier osteoblast-related work (Sabatakos et al, 2000(Sabatakos et al, , 2008Rowe et al, 2009) and selected it for this study because the ENO2 promoter is active in both early osteoblasts (Fig. S1 A) and in more mature osteoblasts in the long bones of adult mice (Fig.…”
Section: Runx2mentioning
confidence: 99%